Energyo 2018
DOI: 10.1515/energyo.0079.00002
|View full text |Cite
|
Sign up to set email alerts
|

Lead exposure from battery recycling in Indonesia

Abstract: In Indonesia, more than 200 illegal used lead acid battery (ULAB) smelters are currently operating. Only a few health studies support the finding of lead-related symptoms and diseases among populations living near the smelters. To assess the blood lead levels (BLLs) and potential health impacts among the population surrounding ULAB recycling smelters, we evaluated health effects reported from 2003 to 2013, conducted focus group discussions with lead smelter owner/workers and a group of 35 female partners of sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Haryanto, for instance, documented 71 distinct smelting locations in the Jakarta metro area. 20 These sites are disparately located in nearly all major areas of the city. 20 Similar spatial diffusion has been identified in those countries where TSIP has been conducted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Haryanto, for instance, documented 71 distinct smelting locations in the Jakarta metro area. 20 These sites are disparately located in nearly all major areas of the city. 20 Similar spatial diffusion has been identified in those countries where TSIP has been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…20 These sites are disparately located in nearly all major areas of the city. 20 Similar spatial diffusion has been identified in those countries where TSIP has been conducted. ULAB operations are of low capital intensity and require little skill.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haryanto assessed the potential health impacts of lead as consequence of the exposure coming from illegal lead acid battery smelters. They found that level of blood lead levels have increased by almost double in the period from 2011 to 2015 (Haryanto, 2016).…”
Section: Leadmentioning
confidence: 99%
“…5,6 The National Institute for Occupational Safety and Health which is also a part of the US Centers for Disease Control and Prevention has designated a blood Pb reference value of 5 mg/dL for occupationally exposed adults. 7 However, cases of adult and childhood Pb poisoning continue to be reported due to association of low Pb-B levels with disease processes such as learning and behavioral deficits, 8,9 cardiovascular 10 and renal 11 disease, decreased fertility, 12,13 and cancer 14 suggesting no safe threshold level for Pb. Pb is known to mimic common divalent metal ions such as calcium (Ca), iron (Fe), zinc (Zn), copper (Cu), and magnesium (Mg), hence altering the biological functions.…”
Section: Introductionmentioning
confidence: 99%